NGHIÊN CỨU ĐỘ NHẠY CẢM KHÁNG SINH CỦA CÁC CHỦNG STREPTOCOCUS NHÓM A, C, G PHÂN LẬP TỪ NHẦY HỌNG HỌC SINH TIỂU HỌC GIAI ĐOẠN 2012 - 2015 - A.G., Nosik; Phạm, Khắc Linh; Vũ, Hoàng Giang; Vũ, Thị Loan; A.V., Dmitriev; Iu.Iu., Ilyasov (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ASSESSMENT OF ANTIBIOTIC SUSCEPTIBILITY IN STREPTOCOCCI GROUPS A, C, G ISOLATED FROM THROAT MUCUS OF PRIMARY SCHOOL PUPILS IN THE PERIOD 2012 - 2015 Antibiotic resistance is a global problem, and serious threat to human health. Study on antibiotic susceptibility in streptococci strains group A, C, G isolated from primary school pupils in Viet Nam during 2012÷2015 showed that all streptococci strains were susceptible to cefalosporins and vancomycin as well, simultaneous resistance to amikacin. The resistant rate of GAS to tetracycline and doxycillin were 70% and 75%, respectively. The rate of erythromycin tolerance of GAS was 52.5% and 40.74% in that of GCS/GGS. The third and fourth generation cephalosporin antibiotic group and vancomycin are considered as essential drugs for treating group A, C and G streptococcal infections. The correlation between mefA and ermTR genes in streptococci genome in the macrolide resistant mechanism were not detected. A tetracycline resistant gene in the jumping gene of the GAS genome was found.